2004
DOI: 10.1111/j.1365-2958.2004.04074.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric structure of the Bacillus subtilis cell division protein DivIVA determined by transmission electron microscopy

Abstract: SummaryDivIVA from Bacillus subtilis is a bifunctional protein with distinct roles in cell division and sporulation. During vegetative growth, DivIVA regulates the activity of the MinCD complex, thus helping to direct cell division to the correct mid-cell position. DivIVA fulfils a quite different role during sporulation in B. subtilis when it directs the oriC region of the chromosome to the cell pole before asymmetric cell division. DivIVA is a 19.5 kDa protein with a large part of its structure predicted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 37 publications
3
87
0
2
Order By: Relevance
“…1B). Consistent with this notion, DivIVA oligomerizes in vitro and in vivo (Muchová et al, 2002;Stahlberg et al, 2004;Oliva et al, 2010), and these oligomers can further assemble into larger structures (Stahlberg et al, 2004;Wang et al, 2009). A 'molecular-bridging' model based on Monte-Carlo simulations argues that the clustering of DivIVA oligomers is favored at more-curved regions owing to the enhanced possibility of stabilizing interactions with the membrane (Lenarcic et al, 2009).…”
Section: Direct Sensing Of Enhanced Curvaturementioning
confidence: 55%
“…1B). Consistent with this notion, DivIVA oligomerizes in vitro and in vivo (Muchová et al, 2002;Stahlberg et al, 2004;Oliva et al, 2010), and these oligomers can further assemble into larger structures (Stahlberg et al, 2004;Wang et al, 2009). A 'molecular-bridging' model based on Monte-Carlo simulations argues that the clustering of DivIVA oligomers is favored at more-curved regions owing to the enhanced possibility of stabilizing interactions with the membrane (Lenarcic et al, 2009).…”
Section: Direct Sensing Of Enhanced Curvaturementioning
confidence: 55%
“…On the other hand, polar localization did not allow us to exclude other functions, like chromosome segregation. The ability of DivIVA BS to oligomerize in vitro, forming elongated particles, the so-called "doggy-bone" structures, has been described previously (34,46). Moreover, DivIVA EF was recently found to self-interact in vivo (43).…”
Section: Discussionmentioning
confidence: 99%
“…An additional characteristic of DivIVA BS is its ability to form oligomers in vitro (34,46), and E. faecalis DivIVA (DivIVA EF ) can self-interact in vivo (43). Nothing is known about the interaction(s) of DivIVA with proteins other than itself.…”
mentioning
confidence: 99%
“…2C, bottom). Previous gel filtration analyses have indicated that purified DivIVA forms octamers and higher-order structures (18,30). Therefore, it seems plausible that the region beyond residue 130 indeed contains the tetramerization domain and that tetramerization is a prerequisite step for octamerization.…”
Section: C-terminal Diviva Truncations Interfere With Minj and Raca Bmentioning
confidence: 99%